Ketiadaan Pencatatan Pernikahan dan Implikasinya terhadap Perlindungan Perempuan dan Anak dalam Masyarakat Perdesaan - N. Mokoagow, Rizaldy; M. Kasim, Nur; Rivaldi Moha, Mohamad (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
Unregistered marriages are still common practice in rural areas of Indonesia, resulting in weak legal protection for women and children within the family structure. Ignorance of the law, local culture, and limited access to marriage registration institutions are the main factors behind this. This study aims to analyze the legal and social impacts of early marriage practices that are not registered at the Religious Affairs Office (KUA), with a case study in Tombolikat Village, Tutuyan District, East Bolaang Mongondow Regency. The method used is a juridical-empirical approach with data collection through interviews with village officials, KUA officials, and couples who have unregistered marriages. The results of the study indicate that the absence of marriage registration causes women to lose their legal legitimacy as wives, so they have no basis for demanding maintenance, inheritance rights, or legal protection in the household. Children born from unregistered marriages also experience losses in legal status, such as the father's name not being listed on the birth certificate, and having no guarantee of inheritance rights and maintenance. In addition, this condition strengthens gender inequality and opens up opportunities for neglect and polygamy without a legitimate legal mechanism. This study recommends the need to strengthen the marriage registration system through community legal education and an integrated marriage confirmation program as a form of inclusive legal protection. The results found that the absence of marriage registration has a serious impact on the loss of legal rights of wives and children, including the right to maintenance, inheritance, and legal recognition. This condition also opens up space for gender inequality, neglect, and the practice of polygamy without legal supervision.